PARADIGMA PENDIDIKAN PEMBEBASAN PAULO FREIRE DALAM KONTEKS PENDIDIKAN AGAMA ISLAM - Robikhah, Aridlah Sendy (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2018)
Education disposed ignoring some liberation values. Human considered like a mechanic machine that must be obey from the system. There is no liberation of thinking, liberation of act, liberation in expression and liberation for giving ideas. Paulo Freire, educational scientist gives some alternative illustrations for liberation pedagogy. This study applied a documentary method. Writer collect some book resources, then classify based on groups (biography, Paulo Freire?s theory and liberation pedagogy in Islamic education). This study found that liberation pedagogy in this case means to have awareness about education and daily life, so what student gets from teacher can be useful for facing their problems. Studying and reading books needs concentration, because according to Paulo Freire?s theory, the essences of study are reinventing, recreating and rewriting. Student must know what learning goals in each themes, because pedagogy is not like banking system,  students are not like an empty box. Students are human that have talent and capability, so this is teacher?s assignment to find and develop student?s ability. When this theory applied in Islamic Study, the solve of some student problems, still have to link to Alquran and Hadis with a double movement principle.